Magnetic shielding systems to support longer-term human exploration of Mars - Pelton, Joseph N.; Green, James (Frontiers in Space Technologies, 2025)
Space activities are primarily conducted for three purposes: scientific research, human space exploration, and space applications. Over the past few decades, commercial space applications have expanded rapidly and now significantly outpace the efforts of space agencies. Agencies such as NASA have largely shifted their focus away from operational applications, leaving this domain to private enterprise. An emerging domain is the integration of scientific research, exploration, and applications: human space development and cosmic defense. This concept includes initiatives such as mitigating space debris, advancing bio-regenerative life support systems for both Earth and space, and enabling infrastructure for future deep space human settlement and enterprise. This article makes the case for an international coalition of space agencies to spearhead this forward-looking effort aimed at altering the Martian environment to support human life. A core feature of this vision involves developing an artificial magnetosphere. This technology would not only support terraforming efforts but could also lead to the establishment of large-scale human colonies on Mars. The concept extends beyond Mars. If successful, magnetic shielding could also be applied to Earth to mitigate catastrophic solar storms or address the long-term degradation of Earth’s geomagnetic field. These activities could yield critical insights into preserving our biosphere and ensuring the future safety of life on Earth. Three broad scenarios are presented to support human life on Mars. Together, they represent a new, integrative approach to space agency missions, one that supports human expansion into deep space and potentially even the revival of Mars as a living world.